Comparative growth performance of some multipurpose tree species of North Western Himalayas - Sharma, J.K.; Gupta, N.K.; Sharma, Sandeep (Indian Journal of Agroforestry, 2020)
The growth attributes like height, dbh and crown spread of fifteen multipurpose tree species at age of 10 years were studied to compare their peformance in mid hill zone of North-Western Himalaya. Among all the species, Melia composita attained the maximum height (9.34m) with m.a.i. and c.a.i. of 0.93 and 1.18m, respectively. It was followed by Acacia mollissima, Grewia optiva and Bauhinia variegata. The radial growth and crown height were also maximum in M. composita. The crown spread and crown area was maximum in Albizia stipulata which excelled over the other species. Ailanthus excelsa recorded the maximum crown index (2.20). Grevillea robusta has obtained maximum positive correlation of dbh and plant height with crown length and crown area. The maximum positive correlation between crown area and crown length was found in Robinia Â pseudoacacia and Sapindus mukorosii while Melia composita recorded maximum positive correlation between crown spread and crown length. The correlations between dbh and plant height, and between plant height and crown length were negative in Bauhinia retusa.